INDUSTRIAL REVOLUTION 4.0 AND GLOBAL CITIZENSHIP EDUCATION IN VIETNAM TODAY - NGUYEN THI, TOAN; LE THI QUYNH, NGA (Advances in Social Sciences Research Journal, 2020)
Beginning with analyzing the nature and effects of the Industrial Revolution 4.0 to the contemporary world, the article shows the impact of this revolution on the formation and development of the generation of global citizens. Thereby, the global citizenship education in Vietnam today which is clarified and reflected in the renovation of high school education and higher education.